Answer:
28.5
Step-by-step explanation:
If you can add brainliest
Please
Use angle sum property (the 3 angles in a triangle sum up to 180°).
2x + x + 54 = 180
3x + 54 = 180
3x = 180 - 54
3x = 126
x = 126/3
x = 42
_____
Hope it helps ⚜
Answer:
(3, -5)
Step-by-step explanation:
Can I please have brainliest?
Answer:
the answer is B
Step-by-step explanation: i added the two fractions
Answer:
x^2 + 18x + 76 + 5 = 0 + 5
Step-by-step explanation:
The first step is to determine the constant that is needed to be able to write the expression in the desired form. That constant is the square of half the x-term coefficient: (18/2)^2 = 9^2 = 81.
The constant that is present is 76, which is 5 fewer than the needed constant, so the "first step" is to add 5 to both sides of the equation:
x^2 + 18x + 76 + 5 = 0 + 5
Then the next step would be to write the left side as a square:
(x +9)^2 = 5 . . . . . . . p = -9; q= 5